2017
DOI: 10.1021/acsami.7b04161
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Sulfides as Intercalation-Type Cathode Materials for Rechargeable Aluminum Batteries

Abstract: We report the electrochemical intercalation−extraction of aluminum (Al) in the layered TiS 2 and spinel-based cubic Cu 0.31 Ti 2 S 4 as the potential cathode materials for rechargeable Al-ion batteries. The electrochemical characterizations demonstrate the feasibility of reversible Al intercalation in both titanium sulfides with layered TiS 2 showing better properties. The crystallographic study sheds light on the possible Al intercalation sites in the titanium sulfides, while the results from galvanostatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
148
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 28 publications
2
148
3
5
Order By: Relevance
“…[67] Similar behaviors could also be observed for Ni 3 S 2 and CuS. [10,12,13,17,[64][65][66][67] Although it is reported that V 2 O 5 delivers specific capacity of 273 mAh g À1 ,i ti sb asically attributed to the side reactions. [37] None of the other cathodes could attain such high specific capacity nor sustain such high current rate.…”
Section: Graphene Versus Other Cathode Materials In Al-ion Cellssupporting
confidence: 55%
See 2 more Smart Citations
“…[67] Similar behaviors could also be observed for Ni 3 S 2 and CuS. [10,12,13,17,[64][65][66][67] Although it is reported that V 2 O 5 delivers specific capacity of 273 mAh g À1 ,i ti sb asically attributed to the side reactions. [37] None of the other cathodes could attain such high specific capacity nor sustain such high current rate.…”
Section: Graphene Versus Other Cathode Materials In Al-ion Cellssupporting
confidence: 55%
“…[10,12,13,17,[64][65][66][67] Although it is reported that V 2 O 5 delivers specific capacity of 273 mAh g À1 ,i ti sb asically attributed to the side reactions. [10,12,13,17,[64][65][66][67] Of greater interest is the ultralong life of the Al-graphene cell with as urvival rate of aq uarter of am illion cycles with Coulombic efficiencya nd capacity retention above 97 %a nd 94 %, respectively. [36] In contrast, the maximum tolerance for current is 0.1 Ag À1 for the rest of the cathodes essentially signifying very low power output.…”
Section: Graphene Versus Other Cathode Materials In Al-ion Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…CR2025‐coin cells were assembled in the glovebox to study the electrochemical property, where Al foil was used as reference electrode, and glass‐fiber paper (435 mm thickness, Whatman 934‐AH) acted as the separator. In order to mitigate corrosion derived from AlCl 3 /[EMIm]Cl electrolyte, titanium foils (0.6 mm thickness, 99.9 %) served as supporters and anticorrosion materials which were attached to both the cathode shell and the anode shell (Figure S1) . The ionic liquid electrolyte was synthesized via mixing anhydrous AlCl 3 and [EMIm]Cl with a 1.1 : 1 molar ratio .…”
Section: Methodsmentioning
confidence: 99%
“…All kinds of carbon materials exhibit a reversible capacity of 60–130 mA h g −1 and unparalleled cycle stability. Transition metal oxides, sulfides and selenides have been reported mainly including Co 3 O 4 , CuO, TiO 2 , SnO 2 , Co 3 S 4 , Co 9 S 8 , CuS, FeS 2 , MoS 2 , Mo 6 S 8 , Ni 3 S 2 , NiCo 2 S 4 , SnS 2 , TiS 2 , VS 2 , Cu 2−x Se and CoSe . These materials could provide a higher capacity, but the cycle stability is inferior than carbon materials.…”
Section: Introductionmentioning
confidence: 99%